Studies toward synthesis of the core skeleton of spiroaspertrione A - Shen, Zhong-Hui; Lu, Si-Yuan; Zheng, Jing-Yun; Zhang, Xiang-Zhi; Peng, Jin-Bao; Ma, Ai-Jun (Frontiers in Chemistry, 2022)
Bioassay-guided isolation of spiroaspertrione A from cultures of Aspergillus sp. TJ23 in 2017 demonstrated potent resensitization of oxacillin against methicillin-resistant Staphylococcus aureus by lowering the oxacillin minimal inhibitory concentration up to 32-fold. To construct this unique spiro[bicyclo[3.2.2]nonane-2,1′-cyclohexane] system, a protocol for ceric ammonium nitrate-induced intramolecular cross-coupling of silyl enolate is disclosed.